Construct validity and reliability of the Finnish version of the Knee Injury and Osteoarthritis Outcome Score - Multanen, Juhani; Honkanen, Mikko; Häkkinen, Arja; Kiviranta, Ilkka (BMC musculoskeletal disorders, 2018)
Background The Knee Injury and Osteoarthritis Outcome Score (KOOS) is a commonly used knee assessment and outcome tool in both clinical work and research. However, it has not been formally translated and validated in Finnish. The purpose of this study was to translate and culturally adapt the KOOS questionnaire into Finnish and to determine its validity and reliability among Finnish middle-aged patients with knee injuries. Methods KOOS was translated and culturally adapted from English into Finnish. Subsequently, 59 patients with knee injuries completed the Finnish version of KOOS, Western Ontario and McMaster Osteoarthritis Index (WOMAC), Short-Form 36 Health Survey (SF-36) and Numeric Pain Rating Scale (Pain-NRS). The same KOOS questionnaire was re-administered 2 weeks later. Psychometric assessment of the Finnish KOOS was performed by testing its construct validity and reliability by using internal consistency, test-retest reliability and measurement error. The floor and ceiling effects were also examined. Results The cross-cultural adaptation revealed only minor cultural differences and was well received by the patients. For construct validity, high to moderate Spearman’s Correlation Coefficients were found between the KOOS subscales and the WOMAC, SF-36, and Pain-NRS subscales. The Cronbach’s alpha was from 0.79 to 0.96 for all subscales indicating acceptable internal consistency. The test-retest reliability was good to excellent, with Intraclass Correlation Coefficients ranging from 0.73 to 0.86 for all KOOS subscales. The minimal detectable change ranged from 17 to 34 on an individual level and from 2 to 4 on a group level. No floor or ceiling effects were observed. Conclusion This study yielded an appropriately translated and culturally adapted Finnish version of KOOS which demonstrated good validity and reliability. Our data indicate that the Finnish version of KOOS is suitable for assessment of the knee status of Finnish patients with different knee complaints. Further studies are needed to evaluate the predictive ability of KOOS in the Finnish population.